Análise da resistência à fadiga entre pilares retos sólidos e anatômicos do sistema cone morse - Santos, Vanessa Tavares de Gois (2014)
Objective: Examine the fatigue resistance of the joint implant-abutment, in straight and anatomical types, submitted to cyclic loads. Material and methods: We used 37 implants (3.75 x 11mm) with morse taper system and 37 abutments, divided into two groups (n = 16: straight abutment, n=21 anatomical abutment, Neodent® Curitiba, Paraná, Brazil). The sets were submitted to cyclic testing using servo-hydraulic equipment, fixing the number of cycles at 5 million. Three sets implant-abutment of each group were subjected to bending tests to determine the maximum load resistance of the samples, which served as a parameter to measure the cyclic tests. We evaluated number of cycles, load and bending moment of the samples. The Fisher’s Test and simple independent test of Mann Whitney were applied. To characterize the survival timings of the test samples, the log-rank test was used. Results: Out of the 31 abutments cyclically tested, 17 (54.8%) fractured in a number of cycles below 5 million established, and 8 (25.8%) belonged to the group of the straight abutments and 9 (29%) of the anatomical abutments, 14 samples (45.2%) resisted the cyclic (5-straight abutments and 9-anatomical abutments). According to Fisher's Exact Test showed no statistical difference between groups (p = 0.394). In relation to the load (N) submitted during the cyclic test, the straight abutments showed larger fracture loads (mean: 566N±59N) that anatomical abutments (mean: 367N±80N). In addition, the minimum and maximum load values occurring in fractured samples of the straight group were higher compared to the anatomical. Regarding the average values of bending moment (Nmm), the Mann Whitney showed variations of the moment in both groups, and the fractured samples behaved slightly significant (p = 0.09). Conclusion: In cyclic fatigue tests, the solid straight abutments obtained average load and bending moment greater than the anatomical abutments. Considering fatigue strength of the fractured samples, there was a significant difference in the load variable and bending moment, with the straight abutment showing higher mean, moreover, for the varying cycles, the two types of abutments (straight and anatomical) behaved mechanically in a similar way.